The conversational implicatures: A case study of the violations of cooperative principles in a novel “Negeri 5 Menara” by Ahmad Fuadi - Bela Fransiska; Farida Ariyani; Ali Mustofa; Eka Sofia Agustina (Aksara: Jurnal Bahasa dan Sastra, 2023)
According to a variety of academic works, implicature is a tool used by pragmatics to address the issue of linguistic meaning. Grice 1975 holds the following opinion. There have been numerous studies on implicature, primarily looking at conventional and conversational implicatures. However, the results of the conversational implicature research in novels, which is characterized by a breach of the cooperative principle, are still ambiguous. As a result, this study aimed to describe the conversational implicatures in Ahmad Fuadi's novel “Negeri 5 Menara” that are marked by violations of the cooperative principles. A qualitative methodology was used to carry out this study. The novel "Negeri 5 Menara" by Ahmad Fuadi served as the study's primary source of data. Conversations between characters that involve violations of the maxims in the cooperation principle serve as the study's source of data. Data were collected by careful reading, looking at sentences with implicatures, selecting, classifying data based on the breach of the violations of the cooperative principles. The collected data were then analyzed descriptively. The study's findings demonstrate that a total of 84 occurrences that violate the cooperative principles were found. The violation of maxims on the principle of cooperation consists of four maxims, namely the maxims of quantity, quality, relation, and manner. The findings have several implications for language education, particularly in the Indonesian context. Limitations and recommendations for furher research are also discussed. Keywords: communication, communicative, literary works, education, Indonesia